2016
DOI: 10.3389/fevo.2016.00089
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships in the Festuca-Lolium Complex (Loliinae; Poaceae): New Insights from Chloroplast Sequences

Abstract: The species within the Lolium/Festuca grass complex have dispersed and colonized large areas of temperate global grasslands both naturally and by human intervention. The species within this grass complex represent some of the most important grass species both for amenity and agricultural use worldwide. There has been renewed interest by grass breeders in producing hybrid combinations between these species and several countries now market Festulolium varieties as a combination of genes from both genera. The two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…Since then, due to the sheer size of the group, usually representative genera were selected for comparative studies to gain an overview on the whole Poodae and their major groupings using morphological data, plastid DNA restriction site analysis, traditional Sanger and, more recently, plastid genome sequencing (Soreng & Davis, 2000;Quintanar & al., 2007;Schneider & al., 2009;Saarela & al., 2015Saarela & al., , 2018Pimentel & al., 2017;Orton & al., 2019). Other studies focused on special groups using an in-depth sampling of taxa, for example, within traditional Aveneae (Grebenstein & al., 1998;Saarela & al., 2010Saarela & al., , 2017Wölk & Röser, 2014 and Poeae Birch & al., 2014Birch & al., , 2017, in which especially the subtribes Poinae (Hunter & al., 2004;Gillespie & Soreng, 2005;Gillespie & al., 2007Gillespie & al., , 2009Gillespie & al., , 2018Refulio-Rodríguez & al., 2012;Hoffmann & al., 2013;Soreng & al., , 2015a, Loliinae (Torrecilla & Catalán, 2002Inda & al., 2008;Cheng & al., 2016;, Sesleriinae (Kuzmanović & al., 2017), Brizinae and Calothecinae (Essi & al., 2008;Persson & Rydin, 2016;Silva & al., 2020) were studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since then, due to the sheer size of the group, usually representative genera were selected for comparative studies to gain an overview on the whole Poodae and their major groupings using morphological data, plastid DNA restriction site analysis, traditional Sanger and, more recently, plastid genome sequencing (Soreng & Davis, 2000;Quintanar & al., 2007;Schneider & al., 2009;Saarela & al., 2015Saarela & al., , 2018Pimentel & al., 2017;Orton & al., 2019). Other studies focused on special groups using an in-depth sampling of taxa, for example, within traditional Aveneae (Grebenstein & al., 1998;Saarela & al., 2010Saarela & al., , 2017Wölk & Röser, 2014 and Poeae Birch & al., 2014Birch & al., , 2017, in which especially the subtribes Poinae (Hunter & al., 2004;Gillespie & Soreng, 2005;Gillespie & al., 2007Gillespie & al., , 2009Gillespie & al., , 2018Refulio-Rodríguez & al., 2012;Hoffmann & al., 2013;Soreng & al., , 2015a, Loliinae (Torrecilla & Catalán, 2002Inda & al., 2008;Cheng & al., 2016;, Sesleriinae (Kuzmanović & al., 2017), Brizinae and Calothecinae (Essi & al., 2008;Persson & Rydin, 2016;Silva & al., 2020) were studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The self-incompatibility and outbreeding features increase genetic variation and complexity in the genus Lolium . Most studies have indicated that the genus can be divided into two groups—an inbreeding group and an outbreeding group—according to morphologic features (Bulinska-Radomska and Lester, 1985 ; Loos, 1993 ; Bennett et al, 2000 ), seed proteins (Bulinska-Radomska and Lester, 1985 ), isozymes and interspecific hybridization (Charmet and Balfourier, 1994 ; Charmet et al, 1996 ), and molecular markers such as restriction fragment length polymorphism (RFLP) and random amplified polymorphic DNA (RAPD) markers (Charmet et al, 1997 ), internal transcribed spacer (ITS) rDNA (Charmet et al, 1997 ; Gaut et al, 2000 ; Catalan et al, 2004 ), sequence-related amplified polymorphism (SRAP) markers (Cheng et al, 2016a ), and chloroplast DNA (Balfourier et al, 2000 ; Cheng et al, 2016b ). In contrast, although both L. rigidum and L. perenne are outbreeding species, among 51 natural populations sampled throughout Europe and the Middle East, most of the L. rigidum populations clustered with those of the three inbred species ( L. temulentum, L. persicum , and L. remotum ), whereas the L. perenne populations could be divided between two different clusters on the basis of chloroplast DNA markers (Balfourier et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…More detailed understanding of phylogenetic relations within the Lolium-Festuca complex was made possible by the applications of chloroplast (e.g., Cheng et al 2016), nuclear DNA markers (e.g. Stammers et al 1995), rDNA nucleotide sequence analysis (e.g., Torrecilla and Catalàn 2002), and markers such as sequence related amplified polymorphism (SRAP) (Cheng et al 2015).…”
Section: Development Of Forage Grass Breeding Using Lolium Festuca mentioning
confidence: 99%
“…Species classification and the nomenclature used within this review have been employed consistently over the last century and appear regularly in publications by most European researchers, including those by the current authors, and are also used widely elsewhere (e.g. in Cheng et al 2016). The term Festulolium conforms to specific EU directives and is applied to all ryegrass/fescue hybrid cultivars, irrespective of their species derivation, and is used in their commercial marketing.…”
Section: Development Of Forage Grass Breeding Using Lolium Festuca mentioning
confidence: 99%
See 1 more Smart Citation